Composite active material for lithium ion secondary battery

The composite active material for lithium-ion secondary batteries, featuring a specific void structure in amorphous carbon, addresses the issue of irreversible capacity and cycle characteristics in conventional materials, providing improved performance and stability.

JP2025065636APending Publication Date: 2025-04-22TOSOH CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023174974
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Conventional composite active materials for silicon-based lithium-ion secondary batteries do not sufficiently alleviate expansion issues during charge and discharge, leading to irreversible capacity and insufficient cycle characteristics.

Method used

A composite active material comprising silicon-based materials and amorphous carbon, where the amorphous carbon has voids consisting of effective and ineffective voids, with a specific ratio of ineffective voids to total voids, reducing irreversible capacity and improving cycle characteristics.

Benefits of technology

The proposed composite active material significantly reduces irreversible capacity and enhances cycle characteristics, making it less prone to structural breakdown during repeated charge and discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065636000002
    Figure 2025065636000002
  • Figure 2025065636000001
    Figure 2025065636000001
Patent Text Reader

Abstract

To provide a composite active material, hardly causing an occurrence of irreversible capacity as compared with conventional composite active materials.SOLUTION: There is provided a composite active material for lithium ion secondary batteries, which contains a silicon-based material and amorphous carbon, the amorphous carbon having voids. The voids comprise either or both of effective voids including the silicon-based material and ineffective voids not including the silicon-based material. In addition, in a cross-sectional observation using a scanning electron microscope, a ratio of the cross-sectional area of the ineffective voids to the total cross-sectional area of the effective voids and the ineffective voids is more than 0% and 25% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composite active material for a lithium ion secondary battery and a method for producing the same. [Background technology]

[0002] As a silicon-based negative electrode active material for lithium ion secondary batteries in which volume change associated with charging and discharging is suppressed, composite active materials (hereinafter simply referred to as "composite active materials") have been investigated which are composed of a silicon-based material such as metallic silicon or a silicon compound and a carbon material, in which the silicon-based material is contained in the carbon material and has a structure in which there are voids between the silicon-based material and the carbon material (Patent Document 1).

[0003] The composite active material disclosed in Patent Document 1 achieves this structure by removing the polystyrene from polystyrene-coated silicon through firing, and the voids between the silicon-based material and the carbon material mitigate the expansion of the silicon-based material that accompanies charging and discharging. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication 2021 / 193662 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the composite active material disclosed in Patent Document 1 does not sufficiently mitigate expansion, and the structure of the composite active material is easily destroyed by repeated charging and discharging. Therefore, when it is assumed to be used as a practical battery, irreversible capacity is easily generated, and the cycle characteristics are insufficient.

[0006] An object of the present disclosure is to provide a composite active material that is less likely to cause irreversible capacity than conventional composite active materials. [Means for solving the problem]

[0007] In this disclosure, the inventors have investigated the improvement of the cycle characteristics of a composite active material. As a result, they have found that the voids in the composite active material do not contain silicon-based materials, and that the irreversible capacity of the composite active material can be reduced by reducing the voids.

[0008] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] A composite active material for a lithium ion secondary battery, comprising a silicon-based material and amorphous carbon, the amorphous carbon having voids, the voids consisting of effective voids containing the silicon-based material and invalid voids not containing the silicon-based material, and further comprising, in cross-sectional observation with a scanning electron microscope, a ratio of the cross-sectional area of ​​the invalid voids to the total cross-sectional area of ​​the effective voids and the invalid voids being greater than 0% and not greater than 25%. [2] The composite active material for a lithium ion secondary battery according to [1] above, wherein a volume ratio of the effective voids to the volume of the silicon-based material is 1 or more and 50 or less. [3] The composite active material for a lithium ion secondary battery according to the above [1] or [2], having an average particle size (D50) of 1 μm or more and 20 μm or less. [4] The composite active material for a lithium ion secondary battery according to any one of [1] to [3] above, wherein the silicon-based material is metallic silicon. [5] The composite active material for a lithium ion secondary battery according to [4] above, wherein the purity of the metallic silicon is 98 mass % or more. [6] A negative electrode comprising the composite active material for a lithium ion secondary battery according to any one of [1] to [5] above. [7] A lithium ion secondary battery having the negative electrode described in [6] above. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide a composite active material that is less likely to cause irreversible capacity compared to conventional composite active materials. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a schematic diagram showing a cross section of the present composite active material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Composite active materials for lithium-ion secondary batteries] Hereinafter, the present disclosure will be described with reference to an example of an embodiment.

[0012] The present embodiment is a composite active material for lithium ion secondary batteries that contains a silicon-based material and amorphous carbon, the amorphous carbon having voids, the voids being composed of effective voids containing the silicon-based material and ineffective voids not containing the silicon-based material, and further, in cross-sectional observation with a scanning electron microscope, the ratio of the cross-sectional area of ​​the ineffective voids to the total cross-sectional area of ​​the effective voids and ineffective voids is more than 0% and 25% or less (hereinafter referred to as the "present composite active material"). As a result, a composite active material that is less likely to cause irreversible capacity can be obtained compared to conventional composite active materials.

[0013] In this embodiment, the silicon-based material is at least one of metallic silicon and a silicon compound, and is preferably metallic silicon. Note that metallic silicon is zero-valent silicon (silicon element).

[0014] The silicon-based material may have the same average particle size (D50) as the pulverized silicon raw material described later. The purity of the metal silicon is not particularly limited, and may be, for example, 98 mass% or more, preferably 2N (99%) or more, and more preferably 4N (99.99%) or more. Although a high purity is preferable, it is sufficient if it is 6N (99.9999%) or less.

[0015] A silicon compound is a compound composed of silicon (Si) and one or more elements other than silicon, and an example of such a compound is silica (SiO2).

[0016] In this embodiment, amorphous carbon refers to carbon in which the half-width of the X-ray diffraction peak of the (002) plane is 3° or more and 12° or less.

[0017] The voids in this embodiment are comprised of effective voids and ineffective voids.

[0018] An effective void is a void in the amorphous carbon in which a silicon-based material exists, whereas an ineffective void is a void in the amorphous carbon in which no silicon-based material exists.

[0019] A schematic diagram of a cross section of the composite active material is shown in Figure 1. In Figure 1, the composite active material (100) is composed of a silicon-based material (10), amorphous carbon (11), effective voids (12), and ineffective voids (13), with the silicon-based material (10) present in the effective voids (12). Furthermore, the silicon-based material (10) is not present in the ineffective voids (13). With this structure, even if the silicon-based material expands upon charging, the volume change is limited to within the voids. Therefore, the expansion and contraction of the composite active material itself upon charging and discharging is suppressed, making it less likely to collapse.

[0020] The number of silicon-based materials contained in each effective gap is 1 or more, and can be 4 or less, or 2 or less, and is preferably 1 or more and 4 or less, or 1 or more and 2 or less.

[0021] The cross section of the present composite active material can be observed by cutting a coated sheet, in which the present composite active material is coated on the surface of a substrate, in an axial direction perpendicular to the coated surface and observing the cut surface.

[0022] The material of the substrate is not particularly limited as long as it does not react with the present composite active material, and examples thereof include one or more selected from the group consisting of copper, aluminum, and nickel.

[0023] The cut surface can be observed using a general scanning electron microscope (for example, device name: JSM-7600F, manufactured by JEOL Ltd.) under the following conditions. Acceleration voltage: 5 kV Magnification: 500x-30,000x

[0024] The cross-sectional areas of the silicon-based material and voids from the obtained cut surface can be calculated using general image analysis software (for example, product name: Nano Hunter NS2K-Pro, manufactured by Nano Systems).

[0025] The cross-sectional areas of the silicon-based material and voids to be measured may be selected at random from the image of the cut surface, and the number of pieces selected is preferably 60±40 from the viewpoint of workability.

[0026] The ratio of the cross-sectional area of ​​the ineffective voids to the total cross-sectional area of ​​the effective voids and the ineffective voids (hereinafter also referred to as "ineffective void ratio") obtained using the above-mentioned image analysis software can be calculated by the following formula (1). (Void void ratio (%)) = (total cross-sectional area of ​​voids (S1)) / ((Total cross-sectional area of ​​ineffective gaps (S1)) + (Total cross-sectional area of ​​effective gaps (S2))) ×100 formula (1)

[0027] In the present embodiment, the void ratio is more than 0%, 1% or more, or 3% or more, and may be 25% or less, 20% or less, or 15% or less, and is preferably more than 0% and 25% or less, 1% or more and 20% or less, or 3% or more and 15% or less. When the void ratio is in this range, the expansion of the composite active material is alleviated, and the volumetric capacity of the composite active material is less likely to decrease.

[0028] The void ratio is the volume ratio of the effective void to the volume of the silicon-based material, and can be calculated by the following formulas (2) to (6) using the cross-sectional area (S3) of the silicon-based material and the cross-sectional area (S2) of the effective void obtained using the image analysis software described above. (Circle equivalent radius of silicon-based material (r1)) = (S3 / π) 1 / 2 Formula (2) (Circular radius of effective gap (r2)) = (S2 / π) 1 / 2 Formula (3) (Volume of silicon-based material equivalent to a sphere (V1)) = (4 × π × r1) / 3 Equation (4) (Effective void volume equivalent to a sphere (V2)) = (4 × π × r2) / 3 Equation (5) (Void ratio)=V2 / V1 Equation (6) The void ratio in this embodiment is 1 or more, 2 or more, or 3 or more, and can be 50 or less, 30 or less, or 10 or less, and is preferably 1 to 50, 2 to 30, or 3 to 10. When the void ratio is within this range, the expansion of the composite active material is alleviated, and the volumetric capacity of the composite active material is less likely to decrease.

[0029] The content of the silicon-based material in the present composite active material is, as the content of silicon (Si) relative to the total mass of the silicon-based material and amorphous carbon, 5% by mass or more or 15% by mass or more, and can be 80% by mass or less or 50% by mass or less, and is preferably 5% by mass or more and 80% by mass or less, or 15% by mass or more and 50% by mass or less.

[0030] The average particle size (D50) in this embodiment may be a particle size corresponding to a cumulative 50% volume diameter (median diameter) in a volume particle size distribution curve measured under the following conditions using a general laser diffraction / scattering type particle size distribution measuring device (for example, device name: SALD7100, manufactured by Shimadzu Corporation). Light source: Semiconductor laser Measurement cell: Batch cell Solvent: Ethanol Refractive index: 3.20

[0031] The average particle size (D50) of the composite active material is 1 μm or more, or 3 μm or more, and may be 20 μm or less, or 15 μm or less, and is preferably 1 μm or more and 20 μm or less, or 3 μm or more and 15 μm or less. The average particle size (D50) of the composite active material is preferably larger than the average particle size (D50) of the silicon raw material.

[0032] The composite active material for lithium ion secondary batteries obtained by this embodiment (the present composite active material) can be used as an electrode active material for lithium ion secondary batteries, preferably as a negative electrode active material, and can also be used in a negative electrode comprising the present composite active material and in a lithium ion secondary battery comprising the composite active material.

[0033] When the present composite active material is used in a negative electrode or a lithium ion secondary battery, the negative electrode and the lithium secondary battery may be produced by any method except for using the composite active material as a negative electrode active material.

[0034] The negative electrode may be an electrode consisting of a negative electrode mixture containing at least the composite active material, a conductive material, and a binder, and a current collector. The conductive material, binder, and current collector may be any material that can be used in a negative electrode for a lithium ion secondary battery, and examples of the conductive material include one or more selected from the group consisting of conductive carbon black, carbon nanofiber, and carbon nanotube, the binder includes one or more selected from the group consisting of polyvinylidene fluoride, styrene butadiene rubber (SBR), carboxymethyl cellulose, and polyacrylic acid, and the current collector includes one or more selected from the group consisting of nickel foil, aluminum foil, stainless steel foil, and copper foil.

[0035] The lithium ion secondary battery may include at least a positive electrode, a negative electrode, an electrolyte, and a separator. The positive electrode, the electrolyte, and the separator may be any material that can be used in a lithium ion secondary battery. For example, the positive electrode may be LiCoO2, LiNiO2, LiNi 1-y Co y O2, LiNi 1-x-y Co x Al yExamples of the positive electrode active material include an electrode having one or more selected from the group consisting of O2, LiMnO2, LiMn2O4, and LiFeO2 as a positive electrode active material; an electrolyte solution containing one or more selected from the group consisting of ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate as a solvent and one or more selected from the group consisting of LiPF6, LiBF4, LiClO4, and LiCF3SO3 as an electrolyte salt; and a separator made of at least one of polyethylene and polypropylene as a separator. [Method of manufacturing composite active material for lithium-ion secondary batteries]

[0036] (Silicon raw material crushing process) The manufacturing method of this embodiment includes a grinding step (hereinafter also referred to as a "silicon raw material grinding step") of grinding a silicon raw material consisting of at least one of metallic silicon and a silicon compound using a grinding solvent to obtain ground silicon raw material.

[0037] The average particle size (D50) of the silicon raw material subjected to the silicon raw material crushing process can be 0.01 μm or more, 0.1 μm or more, or 1 μm, and can be 5 μm or less, 4 μm or less, or 3 μm or less, and is preferably 0.01 μm or more and 5 μm or less, 0.1 μm or more and 4 μm or less, or 1 μm or more and 3 μm or less.

[0038] The average particle size (D50) of the silicon raw material in the production method of this embodiment can be measured using the above-mentioned general laser diffraction / scattering type particle size distribution measuring device.

[0039] The grinding solvent used in the silicon raw material grinding step may be any solvent that does not inhibit the grinding of the silicon raw material, and may be, for example, one or more selected from the group consisting of water, ethanol, methanol, hexane, and toluene, and is preferably at least one of water and ethanol.

[0040] In the silicon raw material crushing step, the silicon raw material is crushed using a crushing solvent, that is, a slurry consisting of the silicon raw material and the crushing solvent (hereinafter also referred to as "silicon raw material slurry") is crushed. Therefore, the crushing in the silicon raw material crushing step is so-called wet crushing, and it is preferable that the wet crushing is performed using a crushing medium such as crushing beads.

[0041] The concentration of the silicon raw material in the silicon raw material slurry, expressed as the mass ratio of the silicon raw material to the mass of the silicon raw material slurry, is, for example, 0.01 mass% or more or 1 mass% or more, and 50 mass% or less or 30 mass% or less, and is preferably 0.01 mass% or more and 50 mass% or less, or 1 mass% or more and 30 mass% or less.

[0042] In the silicon raw material crushing step, the average particle size (D50) of the crushed silicon raw material is 0.005 μm or more, 0.01 μm or more, or 0.05 μm or more, and may be less than 5 μm, 1 μm or less, or 0.6 μm or less, and is preferably 0.005 μm or more and less than 5 μm, 0.01 μm or more and 1 μm or less, or 0.05 μm or more and 0.6 μm or less. With such a particle size, the charge capacity and the initial charge / discharge efficiency are unlikely to decrease due to surface oxidation during charging / discharging, and the particles of the composite active material are unlikely to crack due to volume change due to insertion of lithium ions during charging / discharging.

[0043] The wet grinding time is not particularly limited as long as the ground silicon raw material of the desired particle size is obtained, and the longer the grinding time, the smaller the average particle size (D50) tends to be until equilibrium is reached. The wet grinding time may be appropriately adjusted depending on the amount of silicon raw material slurry to be treated and the grinding method, and may be, for example, 6 hours or more and 30 hours or less.

[0044] The method of wet grinding is not particularly limited as long as it can grind the silicon raw material to a desired particle size, and examples thereof include one or more selected from the group consisting of a ball mill, a bead mill, a roll mill, a colloid mill, and a high-pressure wet opposed collision type disperser, and a bead mill is preferred.

[0045] (Surface modification process) The manufacturing method of this embodiment includes a surface modification step of modifying the surface of the pulverized silicon raw material to obtain a surface-modified silicon raw material. In the surface modification step, a part or all of the surface of the pulverized silicon raw material is coated with silica (SiO2). Since the silica has hydroxy groups on the surface, a surface-modified silicon raw material having hydroxy groups on the surface is obtained in the first step. In the polymer coating step described later, monomers are polymerized from the hydroxy groups on the surface of the surface-modified silicon raw material to form a polymer.

[0046] In the surface modification step, a preferred modification method is a method of mixing a solution containing a silicon raw material, a solvent, a silica source, and a catalyst (hereinafter, also referred to as a "modification solution").

[0047] The solvent may be any solvent that does not inhibit the hydrolysis reaction of the silica source, and examples thereof include one or more selected from the group consisting of water, ethanol, methanol, isopropyl alcohol, propanol, and toluene, and preferably one or more selected from the group consisting of water, ethanol, methanol, and toluene.

[0048] The silica source may be any substance that undergoes a hydrolysis reaction in the presence of a catalyst described below and has a hydroxyl group after the reaction. For example, the silica source may be one or more selected from the group consisting of tetraethoxysilane, tetramethoxysilane, methyltriethoxysilane, and methacryloxypropyltrimethoxysilane, and is preferably at least one of tetraethoxysilane and tetramethoxysilane.

[0049] The catalyst may be any substance that causes a hydrolysis reaction of the silica source, and examples thereof include one or more selected from the group consisting of ammonia, hydrochloric acid, nitric acid, boric acid, and aqueous solutions thereof, and preferably one or more selected from the group consisting of ammonia, hydrochloric acid, and aqueous solutions thereof.

[0050] The treatment conditions in the surface modification step are arbitrary as long as the silica source undergoes a hydrolysis reaction by the catalyst and at least a portion of the silicon raw material can be coated with silica having a hydroxyl group. For example, the reaction temperature can be 20°C or higher or 50°C or higher, and 100°C or lower or 90°C or lower, and is preferably 20°C or higher and 100°C or lower, or 50°C or higher and 90°C or lower.

[0051] (Polymer coating process) The manufacturing method of this embodiment includes a polymer coating step in which a surface-modified silicon raw material is coated with a polymer to obtain a polymer-coated silicon raw material. The polymer coating step produces a pulverized silicon raw material having a polymer on at least a part, preferably the entire, surface of the pulverized silicon raw material ("polymer-coated silicon raw material"). The firing step described below causes the coated polymer to pyrolyze, resulting in a composite active material having a structure with voids.

[0052] A preferred coating method in the polymer coating step is to mix the pulverized silicon raw material, a polymer coating solvent, and a solution containing a monomer and a polymerization initiator (hereinafter also referred to as a "coating solution").

[0053] The solvent for polymer coating may be any solvent that does not inhibit the polymerization reaction of the monomer, and may be, for example, one or more selected from the group consisting of water, ethanol, methanol, isopropyl alcohol, propanol, and toluene, and preferably one or more selected from the group consisting of water, ethanol, and methanol.

[0054] The polymer coated on the pulverized silicon raw material may be any polymer that is thermally decomposed by the firing step described below, and examples thereof include one or more selected from the group consisting of polystyrene, polymethyl methacrylate, polymethyl acrylate, and polyacrylonitrile, with polystyrene being preferred.

[0055] The monomer may be any monomer that serves as a precursor of the polymer, and examples thereof include one or more selected from the group consisting of styrene, methyl methacrylate, methyl acrylate, and acrylonitrile, with styrene being preferred.

[0056] The polymerization initiator may be any one that dissolves in the polymer coating solvent and generates radicals that can initiate polymerization of the monomer, and examples of the polymerization initiator include one or more selected from the group consisting of azobisisobutyronitrile, potassium persulfate, and ammonium persulfate.

[0057] In order to improve the dispersibility of the pulverized silicon raw material, the coating solution may contain a dispersant, such as one or more selected from the group consisting of polyacrylic acid dispersants, styrene sulfonic acid dispersants, and polyvinylpyrrolidone, with styrene sulfonic acid dispersants being preferred.

[0058] The processing conditions in the polymer coating step are arbitrary as long as the polymer can be coated on at least a portion of the surface of the pulverized silicon raw material by polymerization of the monomer. For example, the polymerization temperature may be 20°C or higher or 50°C or higher, and 100°C or lower or 80°C or lower, and is preferably 20°C or higher and 100°C or lower, or 50°C or higher and 80°C or lower.

[0059] The manufacturing method of this embodiment includes a step of separating the slurry after monomer polymerization by centrifugation during the polymer coating step, which removes the polymer that does not have the surface-modified silicon (hereinafter, also referred to as "free polymer"), thereby reducing the invalid porosity.

[0060] Centrifugation may be performed using a general centrifuge (for example, Allegra X-15, manufactured by Beckman Coulter) at the desired rotation speed and time.

[0061] The rotation speed of the centrifuge may be any speed that can precipitate the polymer-coated silicon raw material, and may be, for example, 1000 rpm or more or 2000 rpm or more, and 5000 rpm or less or 4500 rpm or less, and is preferably 1000 rpm or more and 5000 rpm or less, or 2000 rpm or more and 4500 rpm or less.

[0062] The separation time for centrifugation may be any time long enough to precipitate the polymer-coated silicon raw material, and may be, for example, 5 minutes or more, or 10 minutes or more, and 90 minutes or less, or 70 minutes or less, with 5 minutes or more and 90 minutes or less, or 10 minutes or more and 70 minutes or less being preferred.

[0063] After centrifugation, the precipitated polymer-coated silicon raw material (hereinafter also referred to as "precipitate") and the remaining part (hereinafter also referred to as "supernatant") are separated, but the supernatant may be centrifuged again under the above conditions (hereinafter also referred to as "re-centrifugation"). The number of re-centrifugations is not particularly limited as long as the desired precipitate is obtained, but it is preferable to perform re-centrifugation two or more times since the void porosity can be further reduced by further removing the free polymer.

[0064] The polymer-coated silicon raw material obtained by the polymer coating step may have at least a portion of the surface of the pulverized silicon raw material coated with a polymer, and it is preferable that the entire surface of the pulverized silicon raw material is coated with a polymer.

[0065] (Precursor coating process) The manufacturing method of this embodiment includes a precursor coating step of coating a polymer-coated silicon raw material with a carbon precursor to obtain a precursor-coated silicon raw material. The precursor coating step produces a polymer-coated silicon raw material having a carbon precursor on at least a part, preferably the entire, surface of the raw material (the "precursor-coated silicon raw material"). The carbon precursor is converted to amorphous carbon by the firing step described below, and the composite active material is obtained.

[0066] A preferred coating method in the carbon precursor coating step is to mix a polymer-coated silicon raw material, a precursor coating solvent, and a solution containing a carbon precursor monomer and a polymerization initiator (hereinafter also referred to as a "precursor coating solution").

[0067] In order to improve the dispersibility of the polymer-coated silicon raw material, the precursor coating solution may contain a dispersant. Also, the polymer coating solvent, polymerization initiator and dispersant in the above-mentioned polymer coating process can be used.

[0068] (drying process) The manufacturing method of this embodiment includes a step of drying the precursor-coated silicon feedstock (hereinafter, also referred to as a "drying step"). The drying step tends to improve the moldability of the precursor-coated silicon feedstock.

[0069] The drying method may be one or more selected from the group consisting of centrifugation, standing, heating and reduced pressure, and is preferably heating. For example, a heating method may be a method of drying by heating using a spray dryer.

[0070] The heating temperature may be any temperature at which the solvent and physically adsorbed water can be removed, and may be 30°C or lower or 100°C or higher, and may also be 300°C or lower or 250°C or lower, and is preferably 30°C or higher and 300°C or lower, or 100°C or higher and 250°C or lower.

[0071] The heating atmosphere is not particularly limited as long as it does not affect the precursor-coated silicon raw material, and is preferably, for example, one or more atmospheres selected from the group consisting of air, argon, and helium.

[0072] The drying atmosphere may be a flow atmosphere.

[0073] (Spheronization process) The manufacturing method of this embodiment may include a step of forming the precursor-coated silicon feedstock (hereinafter, also referred to as a "spheroidizing step"). The precursor-coated silicon feedstock can be formed into any shape by the spheroidizing step.

[0074] The shape of the precursor-coated silicon raw material after molding is not particularly limited as long as it allows the production of a lithium ion secondary battery, and from the viewpoint of the powder packing density, at least one of a sphere and an approximately sphere is preferable. Note that the approximately sphere does not necessarily have to be an ideal sphere (a perfect sphere), and examples thereof include an elliptical sphere, a sphere with a chipped part, a distorted sphere, and a sphere with an uneven surface.

[0075] The spheronization step may be any step that can mold the precursor-coated silicon raw material into any shape, and may involve the use of impact force, for example, a method that uses impact force generated by the rotation of a rotor.

[0076] The rotation speed of the rotor is 40 m / s or more, or 60 m / s or more, and can be 120 m / s or less, or 100 m / s or less, and is preferably 40 m / s or more and 120 m / s or less, or 60 m / s or more and 100 m / s or less.

[0077] The treatment time may be any time required for the precursor-coated silicon raw material to assume the desired shape, and may be set appropriately depending on the amount of precursor-coated silicon raw material to be subjected to treatment and the treatment method. For example, the treatment time may be 1 minute or more, or 2 minutes or more, and 20 minutes or less, or 10 minutes or less, and is preferably 1 minute or more and 20 minutes or less, or 2 minutes or more and 10 minutes or less.

[0078] (Firing process) The manufacturing method of this embodiment includes a step of calcining the precursor-coated silicon raw material (hereinafter, also referred to as the "calcination step"). As a result, the polymer present on the surface of the pulverized silicon raw material is thermally decomposed to form voids, and at the same time, the carbon precursor is carbonized to become amorphous carbon, thereby obtaining the present composite active material.

[0079] The firing temperature is 300° C. or more or 600° C. or more, and may be 1500° C. or less or 1100° C. or less, and is preferably 300° C. or more and 1500° C. or less, or 600° C. or more and 1100° C. or less. By setting the firing temperature in this range, the polymer on the surface of the pulverized silicon raw material is more easily removed.

[0080] The rate of temperature rise to the firing temperature is 1° C. / min or more, or 3° C. / min or more, and can be 100° C. / min or less, or 50° C. / min or less, and is preferably 1° C. / min or more and 100° C. / min or less, or 3° C. / min or more and 50° C. / min or less.

[0081] The firing atmosphere is not particularly limited as long as it is an oxygen-free atmosphere, and is, for example, one or more selected from the group consisting of nitrogen, argon, and helium, with nitrogen being more preferred.

[0082] The firing atmosphere may be a flow atmosphere. EXAMPLES

[0083] The present disclosure will be described below with reference to examples. However, the present disclosure is not limited to these examples.

[0084] (Preparation of negative electrodes for lithium-ion secondary batteries) A negative electrode mixture obtained by mixing 92.5 mass % of the composite active material, 0.5 mass % of acetylene black (conductive material), and 7.0 mass % of polycarboxylic acid (binder) was mixed with pure water to obtain a negative electrode mixture slurry.

[0085] The obtained negative electrode mixture slurry was applied onto a copper foil of 150 mm in length and 150 mm in width, and after vacuum drying, it was punched out into a circle of 14 mm in diameter. The copper foil carrying the negative electrode mixture was fed at a speed of 1 m / min and a pressure of 4.0 t / cm 2 After roll pressing under the conditions above, the mixture was dried in a vacuum to obtain a negative electrode for a lithium ion secondary battery.

[0086] A lithium ion secondary battery including the obtained negative electrode and having the following configuration was fabricated. Counter electrode: metallic lithium Separator: Polypropylene separator Electrolyte: Solvent Ethylene carbonate:Diethyl carbonate:Fluoroethylene carbonate =1:1:0.04 (volume ratio) Electrolyte: 1.2mol / L lithium hexafluorophosphate Battery type: CR2032 coin cell

[0087] (Calculation of void fraction) The negative electrode for lithium ion secondary batteries was cut by a processing machine using an ion beam, and the cut surface was observed under the following conditions using a FE-SEM (apparatus name: JSM-7600F, manufactured by JEOL Ltd.) to obtain a cross-sectional SEM observation image of the negative electrode for lithium ion secondary batteries. Acceleration voltage: 5 kV Magnification: 30,000x

[0088] Three OHP sheets were placed on top of the printed image of the cross-sectional SEM observation diagram obtained, and the part corresponding to the silicon-based material was traced on the first sheet, the void part where the silicon-based material was present on the second sheet, and the part corresponding to the void part where the silicon-based material was not present on the third sheet. The OHP sheets after tracing were imported into image analysis software (product name: Nano Hunter NS2K-Pro, manufactured by Nano Systems), and the invalid porosity was calculated using the following formula (7). (Void void ratio (%)) = (total cross-sectional area of ​​voids (S1)) / ((Total cross-sectional area of ​​ineffective gaps (S1)) + (Total cross-sectional area of ​​effective gaps (S2))) ×100 formula (7)

[0089] (Cycle characteristic evaluation) The lithium ion secondary battery was used and charged in a thermostatic chamber at 25° C. with a constant current and constant voltage of 0.3 C up to 0.01 V, and then charged at a constant voltage of 0.01 V until the current value reached 0.03 C.

[0090] In addition, "C" indicates the C rate, and 1.0C is the current value that discharges the theoretical capacity calculated from the following formula (8) in one hour. Theoretical capacity (mAh / g) = (theoretical capacity of silicon (4200 mAh / g) × silicon content in the composite active material (%)) + (theoretical capacity of carbon (372 mAh / g) × carbon content in the composite active material (%)) Equation (8)

[0091] Thereafter, the battery was discharged at a constant current of 0.3 C until the voltage reached 1.5 V.

[0092] The above-mentioned charging and discharging steps were defined as one charge-discharge cycle.

[0093] The charge capacity at the nth cycle was defined as the nth charge capacity, and the discharge capacity at the nth cycle was defined as the nth discharge capacity, where n was a positive integer of 1 or more.

[0094] The Coulombic efficiency at the nth cycle was calculated from the nth charge capacity and the nth discharge capacity according to the following formula (9). n-times Coulomb efficiency (%) = 100 x (n-times discharge capacity (mAh / g)) / (n times charging capacity (mAh / g)) Equation (9)

[0095] The n-times full cell equivalent capacity maintenance rate was calculated from the n-times Coulombic efficiency according to the following formulas (10) and (11). Single full cell equivalent capacity maintenance rate (%) = 100 Formula (10) n+1 full cell equivalent capacity maintenance rate (%) = (n full cell equivalent capacity maintenance rate (%)) × (n+1 times Coulomb efficiency (%)) Equation (11) Example 1

[0096] (Silicon crushing process) Metallic silicon and ethanol were mixed so that the metallic silicon concentration was 23 mass %, and this was pulverized for 11 hours in a bead mill using zirconia beads with a diameter of 0.3 mm as the pulverizing medium to produce pulverized silicon slurry with a metallic silicon concentration of 15 mass %.

[0097] (Surface modification process) 121g of pulverized silicon slurry (17.5g of metal silicon), 339g of ethanol, 39g of polycarboxylic acid dispersant, 1.2g of 10mol / L hydrochloric acid, and 140g of distilled water were added and stirred at 250rpm for 30 minutes. After stirring, 35g of TEOS was added, the mixture was heated to 70°C, and stirred at 250rpm for 12 hours to obtain a surface-modified silicon slurry.

[0098] The surface-modified silicon slurry was dispersed in ethanol and then ground for 8 hours in a ball mill using zirconia balls with a diameter of 1.0 mm as the grinding medium. Distilled water was then added to obtain a surface-modified silicon slurry with a surface-modified silicon concentration of 12% by mass.

[0099] (Polymer coating process) 23 g of the surface-modified silicon slurry (2.8 g of metal silicon) and 744 g of distilled water were mixed and substituted with nitrogen. The mixture was then heated to 35°C, 0.105 g of 3-methacryloxypropyltrimethoxysilane was added, and the mixture was stirred at 250 rpm for 30 minutes at 35°C in a nitrogen atmosphere.

[0100] After stirring, 18 g of styrene monomer purified by distillation and 10 mL of LiSS aqueous solution with a lithium p-styrenesulfonate concentration of 0.80% by mass were added, and then the mixture was stirred in a nitrogen atmosphere at 35 ° C. for 2 hours at a rotation speed of 250 rpm. Next, the mixture was heated to 62 ° C., and then 10 mL of APS aqueous solution with an ammonium persulfate (hereinafter also referred to as "APS") concentration of 2.2% by mass was added, and the mixture was stirred in a nitrogen atmosphere at 62 ° C. for 10 hours at a rotation speed of 250 rpm, and the precipitate obtained by centrifuging at 4500 rpm for 25 minutes and the precipitate obtained by further centrifuging twice were all redispersed in distilled water to obtain a polystyrene-coated silicon slurry.

[0101] (Precursor coating process) 420 g of the polystyrene-coated silicon slurry (2.8 g of metal silicon) was mixed with 355 g of distilled water to obtain a slurry, which was then purged with nitrogen, heated to 35°C, and acrylonitrile monomer was added. The mixture was stirred at 250 rpm in a nitrogen atmosphere at 35°C for 2 hours.

[0102] After stirring, the mixture was heated to 62°C and 10 mL of an aqueous APS solution with an APS concentration of 2.2% by volume was added. The mixture was then stirred at 62°C for 10 hours at 250 rpm in a nitrogen atmosphere, and the mixture was centrifuged to recover the precipitate, which was then redispersed in distilled water to obtain a polyacrylonitrile-coated silicon slurry.

[0103] (drying process) The polyacrylonitrile-coated silicon slurry was spray-dried using a three-fluid nozzle type spray dryer under the following conditions to obtain a polyacrylonitrile-coated silicon dry powder. Drying temperature: 200℃ (inlet temperature) Slurry spray rate: 20g / min Dry atmosphere: Air circulating atmosphere Air flow rate: 100L / min Collection method: Cyclone collection

[0104] (Crushing process) The polyacrylonitrile-coated silicon dry powder was pulverized for 3 minutes at a peripheral speed of 100 m / s using a hybridization system (manufactured by Nara Machinery Co., Ltd.) to obtain a substantially spherical polyacrylonitrile-coated silicon powder.

[0105] (Firing process) The roughly spherical polyacrylonitrile-coated silicon powder was packed into a quartz boat and fired in a tubular furnace under the following conditions. Firing method: Normal pressure firing Firing atmosphere: Nitrogen flow atmosphere (gas linear velocity 38 cm / min) Holding temperature: 1100℃ Holding time: 1 hour Heating rate: 5℃ / min

[0106] In this way, a composite active material for a lithium ion secondary battery of this example was obtained.

[0107] The composite active material for a lithium ion secondary battery of this example had a void ratio of 2.4 and an average particle size (D50) of 5 μm.

[0108] Comparative Example 1 (drying process) The polyacrylonitrile-coated silicon slurry obtained in the same manner as in Example 1 was dried overnight at 70° C. under vacuum in a vacuum dryer to obtain a polyacrylonitrile-coated silicon dry powder.

[0109] (Crushing process) The polyacrylonitrile-coated silicon dry powder was placed in a blade mill and pulverized for 150 seconds at a rotation speed of 15,000 rpm while being cooled with water, to obtain a substantially spherical polyacrylonitrile-coated silicon powder.

[0110] A composite active material for a lithium ion secondary battery of this comparative example was obtained in the same manner as in Example 1, except that the obtained substantially spherical polyacrylonitrile-coated silicon powder was subjected to a firing step.

[0111] The composite active material for a lithium ion secondary battery of this comparative example had a void ratio of 2.6 and an average particle size (D50) of 24 μm.

[0112] Comparative Example 2 (Polymer coating process) 152 g of the same surface-modified silicon slurry as in Example 1 (8.3 g of metal silicon) and 621 g of distilled water were mixed and substituted with nitrogen. The mixture was then heated to 35°C, 0.315 g of 3-methacryloxypropyltrimethoxysilane was added, and the mixture was stirred at 250 rpm for 30 minutes at 35°C in a nitrogen atmosphere.

[0113] After stirring, 53 g of styrene monomer purified with a polymerization inhibitor remover and 10 mL of LiSS aqueous solution with a lithium p-styrenesulfonate concentration of 0.60% by mass were added, and the mixture was stirred at 250 rpm for 2 hours at 35°C in a nitrogen atmosphere. Next, the mixture was heated to 62°C, and 35 mL of ammonium persulfate (hereinafter also referred to as "APS") aqueous solution with a concentration of 0.56% by mass was added at a rate of 3.5 mL / hr, and the mixture was stirred at 250 rpm for 10 hours at 62°C in a nitrogen atmosphere. This resulted in a polystyrene-coated silicon slurry.

[0114] A composite active material for a lithium ion secondary battery of this comparative example was obtained in the same manner as in Example 1, except that the obtained polystyrene-coated silicon slurry was subjected to the precursor coating step.

[0115] The composite active material for a lithium ion secondary battery of this comparative example had a void ratio of 1.7 and an average particle size (D50) of 5 μm.

[0116] The evaluation results of the composite active materials obtained in the examples and comparative examples are shown in the table below.

[0117] [Table 1] From Table 1, the invalid porosity of Example 1 was lower than those of Comparative Examples 1 and 2. Therefore, it was confirmed that the invalid porosity can be reduced by performing centrifugation after the polymer coating step.

[0118] In addition, the capacity maintenance rate converted into 25 full cells showed a higher value than Comparative Examples 1 and 2. Therefore, it was confirmed that the cycle characteristics were improved by reducing the invalid porosity.

Claims

1. A composite active material for a lithium ion secondary battery, comprising a silicon-based material and amorphous carbon, the amorphous carbon having voids, the voids consisting of at least one of effective voids containing the silicon-based material and invalid voids not containing the silicon-based material, and further comprising a composite active material for a lithium ion secondary battery, the ratio of a cross-sectional area of ​​the invalid voids to a total cross-sectional area of ​​the effective voids and the invalid voids being greater than 0% and not more than 25%, when observed in cross-section with a scanning electron microscope.

2. 2 . The composite active material for a lithium ion secondary battery according to claim 1 , wherein a volume ratio of the available voids to a volume of the silicon-based material is 1 or more and 50 or less.

3. 3. The composite active material for a lithium ion secondary battery according to claim 1, having an average particle size (D50) of 1 μm or more and 20 μm or less.

4. 3. The composite active material for a lithium ion secondary battery according to claim 1, wherein the silicon-based material is metallic silicon.

5. 5. The composite active material for a lithium ion secondary battery according to claim 4, wherein the purity of the metallic silicon is 98 mass % or more.

6. A negative electrode comprising the composite active material for a lithium ion secondary battery according to claim 1 or 2.

7. A lithium ion secondary battery comprising the negative electrode according to claim 6.

Citation Information

Patent Citations

  • Composite active material for lithium secondary battery, electrode composition for lithium secondary battery, lithium secondary battery electrode, and method for manufacturing composite active material for lithium secondary battery

    WO2021193662A1